2012
DOI: 10.4236/ajor.2012.22024
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Algorithm for the Split Delivery Vehicle Routing Problem

Abstract: The Split Delivery Vehicle Routing Problem (SDVRP) allows customers to be assigned to multiple routes. Two hybrid genetic algorithms are developed for the SDVRP and computational results are given for thirty-two data sets from previous literature. With respect to the total travel distance and computer time, the genetic algorithm compares favorably versus a column generation method and a two-phase method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
0
23
0
1
Order By: Relevance
“…It can be observed that SplitILS was capable of improving the result of 243 instances and equal the result of another 55. [38]. e Moreno et al [28].…”
Section: Summary Of the Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It can be observed that SplitILS was capable of improving the result of 243 instances and equal the result of another 55. [38]. e Moreno et al [28].…”
Section: Summary Of the Resultsmentioning
confidence: 96%
“…More recently, Wilck IV and Cavalier [37] developed a two-phase constructive procedure for the SDVRP-LF. They also proposed a Genetic Algorithm [38] for the same variant.…”
Section: Related Workmentioning
confidence: 98%
“…It is not hard to find that the value of [ min , max ] has not much influence on solutions, and average gap between [2,4], when 40 < / ≤ 100, the value is [3,5] or [3,6], and when / is more than 100, the value is [3,7].…”
Section: Computational Experimentsmentioning
confidence: 99%
“…In common sense, Vehicle Routing Problem is defined as follows: how to determine appropriate delivery routes between series of collection and reception terminals and guarantee delivery vehicles in a proper order, so as to satisfy some requirements (e.g., shortest distance, minimum cost, delivery time, and needed vehicles) within kinds of constraints, such as amount of goods, sending time, vehicle capacity, mileage restriction, and time limitation. Currently, VRPs have been identified in many applications, such as products outbound distribution scheduling [1], home care crew scheduling [2], newspaper delivery [3], school bus routing [4], cargo routing [5], airline crew scheduling [6], waste collection scheduling [7], service system design [8], and computer system integration [9].…”
Section: Introductionmentioning
confidence: 99%
“…Derigs et al (2010) and Wen et al (2015) presented a local search-based metaheuristics for the SDVRP. Wilck IV et al (2012) offered a genetic algorithm for the split delivery vehicle routing problem while Khmelev and Kochetov (2015) built a hybrid VND method for this problem. Zhang et al (2012) studied SDVRP for emergency logistics and proposed an evolutionary heuristic approach to solve such problem.…”
Section: Introductionmentioning
confidence: 99%